Analisis penerapan UI/UX dalam aplikasi media sosial: Dampaknya terhadap keterlibatan pengguna dan loyalitas platform - Subhan, Subhan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This research focuses on applying UI/UX design principles in social media applications and analyzing their impact on user engagement and platform loyalty in the long term. With increasing competition among social media platforms, user experience has become a major determining factor in app success. This research explores how UI/UX elements such as efficient navigation structure, consistent visual aesthetics, interface responsiveness, and content personalization play a role in increasing user engagement, time spent on the app, and user intent to return to the platform. Using quantitative and qualitative approaches, data was collected through user surveys and analysis of behavioral data from several leading social media platforms. The research results show that optimal UI/UX design not only significantly influences user engagement levels, but also increases user loyalty, reduces churn rates, and increases retention in the long term. This study provides strategic recommendations for social media application developers in designing interfaces that support sustained engagement and positive user experiences